ANALISIS KINERJA STRATEGI PASAR DAN BAURAN PEMASARAN TERHADAP KEPUTUSAN MENGUNJUNGI OBJEK WISATA DI KABUPATEN KUNINGAN - Angga Sucitra Hendrayana; Imas Maesaroh (Jurnal Manajemen Bisnis Performa, 2017)
Tourism is one of the drivers of the world economy that proved able to contribute to the prosperity of a country. Tourism development is able to stimulate business activities resulting in significant benefits for a country. With the existence of regional autonomy demands regional independence in managing its own regional assets, one of which is the tourism sector. Each region in Indonesia has different characteristics in terms of demographic, geographical and cultural, it becomes the potential of the tourism sector of each region. So that each region will compete to get income to improve the welfare of each region and move the wheels of the economy. For that needed a market strategy to increase the number of tourist visits to the tourist object in the destination area. One of the market strategies as a product or service marketing strategy is STP (Segmentation, Targeting and Positioning). Objects studied is the performance of market strategies and marketing mix on the tourist attraction in Kabupaten Kuningan. This research was conducted with a research design to obtain a description of the performance of market strategy and marketing mix of the decision to visit the tourist attraction in Kabupaten Kuningan. Research method used in this research is explanatory survey method, that is research method done by explaining the causal relationship between variables through hypothesis testing. Surveys were conducted by taking samples from one population and using questionnaires as data gathering tools. The results of the study showed that market strategy performance had significant relationship with marketing mix with strong moderate relationship. The result of research shows that the performance of market strategy has a significant effect on the decision to visit tourist object in Kabupaten Kuningan   with total influence of 31,4%, consist of direct influence equal to 20,6% and indirect influence equal to 10,8%. The results showed that the marketing mix significantly influenced the decision to visit the tourist attraction in Kabupaten Kuningan with a total influence of 34.8%, consisting of a direct influence of 24.0% and indirect influence of 10.8%. The results showed that the performance of market strategy and marketing mix together significantly influence the decision to visit the tourist attraction in Kabupaten Kuningan with a total influence of 66.3%, while the remaining 33.7% is the influence of other variables that are not observed in this research.